DISKURSUS GENDER DALAM PENDIDIKAN ISLAM - Iqbal, Mahathir Muhammad (Analisis: Jurnal Studi Keislaman, 2015)
Our  religious  orientation  today  is still  dominated  by the  bias of the normative discourse of women’s interests. Especially regarding   gender  relations.   We   actually   realize   that   many religious  law,  personal law  such  families,  religious  practices, and including  also the  social and political  leadership  over  the legitimacy  of religious  especially  for women,  is  based  on  the assumption  of patriarchy  and sexism.  The system  is based  on patriarchy  and sexism, usually alienate  women at home, so men are more able to dominate  women. Gender discourse in Islamic education  clearly  has  a very  important  relevance.  In fact,  the discourse of gender and sexism can be on the agenda the study of new forms  of equality  and egalitarianism  represents  justice discourse.  This gender studies,  for example,  can be used as an alternative   paradigm  construction   amid   strong   conservative currents would strive to restore the role of women to the domestic sector, with a variety of pragmatic legitimacy, religious, or ideological  science. One of the immediate  urgent effort  is how to  formulate  a  concept  of  gender  oriented  Islamic education